2018
DOI: 10.1521/aeap.2018.30.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of HIV Stigma on Psychosocial Well-Being and Substance Use Behaviors Among People Living With HIV/AIDS In China: Across the Life Span

Abstract: To date, existing studies have indicated that stigma against people living with HIV/AIDS (PLWHA) negatively affects their psychosocial well-being, and the impact may differ by age. In the current study, we aim to assess the impact of various types of stigma on PLWHA’s psychological status and concomitant substance use. We explored different types of HIV stigma with psychosocial well-being and substance use employing mixed effect models among 2,987 Chinese PLWHA. Multivariate analyses revealed that each type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…HIV-related stigma may impact negatively on the uptake of HIV services as well as psychosocial well-being of PLHIV 1,15. The South African National AIDS Council (SANAC) has noted that HIV stigma and discrimination of PLHIV need to be tackled, and consequently commissioned a national PLHIV Stigma Index study 16.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-related stigma may impact negatively on the uptake of HIV services as well as psychosocial well-being of PLHIV 1,15. The South African National AIDS Council (SANAC) has noted that HIV stigma and discrimination of PLHIV need to be tackled, and consequently commissioned a national PLHIV Stigma Index study 16.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar with previous studies. For example, Zhang et al [ 38 ] argued that PLWH who experience discrimination are likely to have worse physical and psychological health status (e.g., distress and anxiety), which are highly related to inferior employment outcomes. Analogously, Su et al [ 26 ] asserted that social support can help reduce negative psychosocial consequences of the HIV experiences, thereby benefiting for superior employment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We first found that older PLWH can better leverage the undesirable effects of negative self-image and workplace discrimination on employment quality. It may be explained that older PLWH are more likely to use adaptive coping strategy in dealing with burden from negative self-image and workplace discrimination compared with their younger peers [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although health care contexts should be "safe and protective" spaces, PLHIV are frequently subjected to refusal of care, irrational use of infection control measures by care providers [10][11][12], violation of their confidentiality, unconsented testing and disclosure of HIV status, and verbal abuse [10,[13][14][15][16], while seeking care. The detrimental effects of stigma on the health outcomes of PLHIV are well documented [17], such as higher risktaking behaviour [18,19], refusal to disclose the HIV status [20], low uptake of HIV testing, care and support services [21][22][23][24], and poor adherence to treatment [25][26][27]. Stigma also undermines the mental health and quality of life PLHIV [19,28].…”
Section: Introductionmentioning
confidence: 99%
“…The detrimental effects of stigma on the health outcomes of PLHIV are well documented [17], such as higher risktaking behaviour [18,19], refusal to disclose the HIV status [20], low uptake of HIV testing, care and support services [21][22][23][24], and poor adherence to treatment [25][26][27]. Stigma also undermines the mental health and quality of life PLHIV [19,28]. These concerns are the rationale for the increased efforts to combat the HIV stigma in general and specifically in health settings [29].…”
Section: Introductionmentioning
confidence: 99%